Recurrent infestation with pediculosis capitis among aged 10-11 students in Hulu Langat, Selangor - Mohd Tohit, Nor Faiza; Lekhraj, Rampal; Lye, Munn Sann; Lim, Poh Ying; Muhamad Saliluddin, Suhainizam (Department of Community Health, Faculty of Medicine and Health Sciences, University Putra Malaysia, 2018)
Background: Recurrent Pediculosis capitis may lead to various physical, economical and psychological consequences. The aim of the study was to determine the level of recurrent Pediculosis capitis, identify the factors associated with the recurrence and its predictors. Materials and Methods: The study used cross-sectional study design. Ten schools were included in the study. A total of 4,390 students from standard four and five were screened for Pediculosis capitis. Only 308 students diagnosed with Pediculosis capitis were included and treated. After 6-weeks, the recurrent infestation level was determined. Result: The total level of recurrent infestation was 8.30%. Contact with person with lice infestation was associated with recurrent Pediculosis capitis (χ2 = 3.557, df =1, P = 0.050). Hair type (χ2 = 4.388, df =1, P = 0.036) and hair length (χ2 = 4.225, df =1, P = 0.040) showed significant association with recurrent Pediculosis capitis. Those with previous contact with an infested person had odds of 3.263 to have recurrent infestation at 6-weeks as compared to those without previous infestation (AOR=3.262, 95% CI = 1.138 – 9.356, P=0.028). The respondents with curly hair had the odds of 2.89 times higher than those with straight hair to have recurrent infestation at 6-weeks (AOR = 2.895, 95% CI = 1.155 -7.257, P = 0.023). Conclusion: The total level of recurrent infestation was 8.30%. It is associated with contact with person with Pediculosis capitis, hair type and hair length. Recurrent Pediculosis capitis is still a public health problem and necessary intervention must be taken to prevent or reduce its occurrence.